2004
DOI: 10.1007/bf03018781
|View full text |Cite
|
Sign up to set email alerts
|

The callander laryngoscope blade modification is associated with a decreased risk of dental contact

Abstract: P Pu ur rp po os se e: : Dental damage may occur with laryngoscopy. The purpose of this study was twofold: to determine whether preoperative examination could predict the risk of contacting the teeth with the laryngoscope and to evaluate the effectiveness of a modified Macintosh blade on reducing dental contact.M Me et th ho od ds s: : Four hundred and eighty-three patients scheduled for elective surgery requiring general anesthesia with endotracheal tube placement were studied prospectively. Features that mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 11 publications
2
37
1
1
Order By: Relevance
“…In accordance with other studies 9,[11][12][13][14] the distance between flange and teeth was increased significantly, while the visibility of laryngeal structures was improved in comparison to the original Macintosh blade. According to Lockhart et al, 15 51% of dental traumas in anesthesiology occur during tracheal intubation by contact of the laryngoscope's flange with the maxillary left incisor.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In accordance with other studies 9,[11][12][13][14] the distance between flange and teeth was increased significantly, while the visibility of laryngeal structures was improved in comparison to the original Macintosh blade. According to Lockhart et al, 15 51% of dental traumas in anesthesiology occur during tracheal intubation by contact of the laryngoscope's flange with the maxillary left incisor.…”
Section: Discussionsupporting
confidence: 91%
“…6 So far, no single approach has proven to be superior with respect to the prevention of tooth damage. Although larger controlled trials, comparing different laryngoscopes with regard to laryngeal visibility 19 or frequency of bladetooth contact 11 have been conducted, trials with dental injury damage as a primary outcome parameter would be ethically challenging, and are still lacking. Finally, the majority of patients in this study did not feature any airway abnormalities, and our results may not be applicable to patients with difficult airways.…”
Section: Discussionmentioning
confidence: 99%
“…From our previous observations, the mean blade-tooth distance when using the conventional left-handed laryngoscope was 2.0 mm with a standard deviation (SD) of 1.8 mm [3]. As- …”
Section: Thismentioning
confidence: 93%
“…When the blade of the laryngoscope is precisely positioned on the vallecula with refined control of the laryngoscope, and the lower chin is lifted with a firm push upward, the laryngoscope can have maximum visibility, and pushing in the tube would be much easier. Additionally, the distance from the teeth to the blade of the laryngoscope could be maximized with the strength that lifts up the lower chin, minimizing the risk of damage to the teeth [3,4]. Therefore, it would be reasonable to allow the operator to use his/her right hand if he/she is right-handed and the left hand if he/she is left-handed to control the laryngoscope.…”
mentioning
confidence: 99%
“…63,64,69 -72 When a satisfactory view of the glottis is difficult to obtain during laryngoscopy, the patient's maxillary anterior teeth are sometimes used as a fulcrum by the laryngoscope blade, which can lead to a dental injury. 73 When a tooth's natural structure has been compromised by decay or the placement of a restoration, it becomes proportionally weaker and more prone to injury. 74,75 Newland et al 76 found that patients with poor dentition or reconstructive work were 3.4× more likely to have dental injuries related to anesthesia.…”
Section: Perioperative Dental Damagementioning
confidence: 99%